The economic effects of refugee return - Uri Dadush (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The recent surge in the number of forcibly displaced persons who cross international borders in search of protection has prompted interest in evaluating policies that achieve the possible 'end points' of the phenomenon. These are the integration of the forcibly displaced persons in the country of destination, relocation in a third country, and return to the country of origin. The focus of this paper is on the third aspect, and more specifically on the appropriateness of return policy viewed from an economic perspective. Although the vast majority of forcibly displaced people is found in developing countries, the object of this paper are the return policies of advanced countries.
Keywords: F22; F66; J61; 330; refugees; return; migration; integration; displacement; forced; repatriation; deportation